Calculation of load capacity and stability of moderately slender and slender axial loaded circular CFT columns - Lazović Marija; Deretić-Stojanović Biljana; Radovanović Janko (Građevinski Materijali i Konstrukcije, 2018)
In this paper, results of experimental investigation of bearing capacity and stability of slender and moderately slender CFT circular tubes are presented. The effects of ratio thickness/ radius of steel cross section and support conditions are investigated. Numerical simulation for the tested examples was performed in computer program ABAQUS. In this simulations, nonlinear constitutive models were used for modelling of concrete, steel and concrete/steel connection. With modified Rick's method critical buckling force for the CFT column was calculated. Verification of the obtained experimental results was performed with comparison with several world standards: EC4, ACI, AS, AISC, as well as with the results obtained in ABAQUS.